Visionary Critique: Gender, Self and Relationship in Rosetta and Two Days, One Night Journal for Religion, Film and Media - Stefanie Knauss (Journal for Religion, Film and Media, 2016)
The films of Jean-Pierre and Luc Dardenne stand out for their complex, multi-dimensional female and male characters whose representation disrupts gender stereotypes in numerous ways, both in how the characters themselves are depicted and how they are shown to relate to other individuals and their social context. In this contribution, I will explore the themes of self, relationship, solidarity, family and work - all of them recurring issues in the films by the Dardennes - using gender as my primary category of analysis, and focusing in particular on the treatment of these themes in Rosetta (Jean-Pierre and Luc Dardenne, FR/BE 1999) and Deux jours, une nuit (Two Days, One Night, Jean-Pierre and Luc Dardenne, BE/FR/IT 2014). I will argue that whereas Rosetta offers a critique of the damaging effects of the masculinized capitalist system on individuals and their relationships, Two Days, One Night can be understood as a vision of alternative possibilities of solidarity and women's empowerment and agency even within the persistent context of masculinized capitalism.